Transformative Education Research Conference – An Incredible Learning Opportunity - Khadka, Kausalya D.; Manandhar, Anupama (Journal of Education and Research, 2017)
This non-refereed contribution to the special issue of Journal of Education and Research is a joint reflective note which describes the personal contexts and experiences of the two Masters of Ceremony at the First International Conference on Transformative Education Research and Sustainable Development (TERSD) held on 21-23 October 2016 in Dhulikhel, Nepal. We, one after the other, without any formal background to the paper, relate our own individual experiences and learning of the event. More specifically, we have portrayed our personal journeys to the international conference hall, and described our reflective ideas and feelings on running the three-day event among the national and international research scholars and delegates. We conclude with some final thoughts on how we could embrace the learning opportunity and by making a commitment to joining the transformative education community.